Optimizing harvesting procedures of Amaranthus hybridus L. and A. tricolor L. under different watering regimes during hot and cool seasons in southern Mozambique - Ribeiro, Jeronimo E. M. M. (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.